Influence of uterine manipulator on oncological outcome in minimally invasive surgery of endometrial cancer: A systematic review and meta-analysis. Issue 10 (October 2022) - Scutiero, G.; Vizzielli, G.; Taliento, C.; Bernardi, G.; Martinello, R.; Cianci, S.; Riemma, G.; Scambia, G.; Greco, P.
Abstract: Aim: The endoscopic approach for early-stage endometrial cancer (EC) treatment is considered gold standard. Some authors expressed their concern regarding uterine manipulator (UM) as a risk factor for tumor spillage and dissemination allowing peritoneal or lympho-vascular spaces invasion (LVSI). This meta-analysis aimed to evaluate the effect of UM on the presence of LVSI, recurrence rate and presence of atypical or malignant peritoneal cytology in patients with endometrial cancer. Methods: We searched electronic databases including PubMed, MEDLINE, Embase, Scopus, EBSCO, Google Scholar, and ClinicalTrials.gov . The pooled results were used to evaluate the association between the use of UM and oncological outcomes. This systematic review was reported according to PRISMA statement 2020. Statistical meta-analysis was performed using Review Manager software. Results: This systematic review included 18 studies (3 prospective studies, 13 retrospective studies, and 2 RCT). The pooled results showed no significant difference (RR: 0.86, 95% CI, 0.69 to 1.08) in the incidence of LVSI between manipulated hysterectomy and total abdominal hysterectomy (TAH) and between UM group and non-UM group in minimally invasive surgery (RR: 1.18, 95% CI, 0.76 to 1.85), no significant difference in the rate of recurrence (RR: 1.11, 95% CI, 0.71 to 1.74), in the incidence of positive peritoneal cytology between manipulated and non-manipulated hysterectomies in minimally invasive surgery (RR: 1.89, 95% CI, 0.74 to 4.83) and before and after the use of uterine manipulator (RR: 1.21, 95% CI, 0.68 to 2.16). We found a positive association between malignant cytology and hysterectomies in which a uterine manipulator had been used in a sub-group analysis where LH/LAVH were compared to TAH. (RR = 2.26, 95% CI, 1.08–4.71. P = 0.03). Conclusions: This meta-analysis supports that the use of uterine manipulator for minimally invasive treatment of endometrial cancer does not increase the rate of recurrence and LVSI. Therefore, the opportunity of any other studies on its use in endometrial cancer women should be questioned.